Analysis of the Anthropogenic Probability of Forest Fires inthe Tempisque Conservation Area, Costa Rica: An ApproachBased on Weights of Evidence and Landscape Metrics - Farfán, Michelle (2025)
This study analyzes the relationship between forest fires and landscape fragmentation in the Tempisque Conservation Area (ACT) and the Chorotega Biological Corridor (CBCh), Costa Rica. Using MODIS satellite data (2000-2024) and landscape metrics, a 62.96% increase in wildfires was observed in the last decade, especially in fragmented areas with low forest cover and high edge density. The estimated size of forest fragments with a high probability of anthropogenic ignition was 6.26 ha. The northern zone of the ACT showed a higher probability of fires and fragmentation than the southern zone. The results are crucial for developing fire prevention and management strategies, promoting community resilience to climate change.